THE IDENTIFICATION AND STRUCTURE CONTROL OF LIMESTONE DEVELOPMENT IN N11-N14 INTERVAL NGIMBANG SUB BASIN - Imanuel Sebayang, Rio
Paleogen Ngimbang Sub Basin is a part of North East Java Basin which is located in the eastern part to southeast of East Cepu High. The east part of this Sub Basin is bordered by Kemandung Ridge with orientation northeast – southwest, and it seems to be controlling the development of half graben, with a slope face to the northwest. In that area, there are not many researches done to find the presence of N11-N14 limestone, which was proven to be in Tapen-1 well. The background of this research is the result of 2D seismic acquisition in 2007 in the research area which shows the presence of Middle Miocene coral limestone buildup reflection pattern at N11-N14 lifespan. The method used in this research is divided into two parts which is done in parallel, which are confirming the probability of the form of limestone in 2D seismik data by using seismik attribute and isochrone map, then proving the presence of limestone in the research area by geology analysis, which is by analyzing the development of the structure. The analysis of seismik attribute shows the reflection pattern of mounded form, along with the onlap which grows on limestone’s buildup. The reconstruction of structure which is made at the 2D seismik data shows the elevation event from N9 to N14 lifespan, when research area that used to be insides, is kept on elevating until it becomes shelf at N11 lifespan. This analysis is also supported by the burial history data of Ngimbang-1 well. Then from the sequence stratigraphy analysis, using the log Gamma Ray data of Tapen-1, it shows that there is a repetition of several HST phases, which enables the development of limestone in the research area. From the research analysis, it can be concluded that N11-N14 limestones develop in shelf environment in the research area.